The linguistic expression of power in political addresses of Polish prime ministers from 1945 to 2019 (quantitative analysis) - Citlak Amadeusz; Kozioł Pamela (Psychology of Language and Communication)
The current study presents a quantitative analysis of the political addresses of 29 Polish prime ministers in the light of the theory of the desire for power. The timeframe covers 74 years, between 1945 and 2019, including two important periods in Polish history: Soviet domination (1945-1989) and the time since the fall of communism and the return of an independent Poland (1989-2019). An analysis of the vocabulary grid adopted in our preliminary and main study allowed the identification of different views of social relations and the social world. The concept of power provided a consistent explanation of the captured quantitative differences in the addresses: first, differences in language from the communist era and independent Poland after 1989; second, differences in language from the periods of breakthroughs in the country’s history (martial law, overthrow of communism, accession to NATO and the EU); third, in the addresses of the prime ministers representing different parties and political ideologies (Civic Platform and Law and Justice).